(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
This article discusses the importance of developing the spiritual competence of future teachers, and comments on the reform of today’s modernized education system, the updating of textbooks, and the application of foreign experiences to the pedagogical process. Also in the article, there are views on the importance of improving the competence level of future teachers in the American education system and the European education system, and the main idea of the concepts of pedagogical innovation is explained in the article. The article served to illuminate the theoretical and practical peculiarities of pedagogical competence.